A Study on Biomass Production of Yeast Isolated from Starter Culture (Sa Lao) - Botthoulath, Viengvilaiphone; Keohavong, Bounmy (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
Yeast species has been studied intensively and widely used in industrial, particularly food and beverage fermentation, Bakery, and enzyme production. The aims of this project were to isolate yeast strains from local starter cultures of Savannakhet Province, determine the optimal medium components and cultivation condition for their biomass production and evaluate the nutritional values of the biomass. Two different yeast strains were isolated from two yeast starter cultures purchased from local markets in Savannakhet Province. Based on their colony and cell morphologies, were assumed identified as Saccharomyces. Cerevisiae Y1 and Y2. Based on their biomass production, Y1 was selected for further experiments. The optimization of yeast biomass production was carried out using conventional method of which one factor was varied at a time. Carbon sources and carbon concentrations were found to be the major factors affecting the biomass production, the optimized conditions for yeast growth were found as 40g/l of glycerol, pH 5 and incubation time of 48 h. Under these conditions, the biomass production was 6.78 g/l. Additionally, nutritional analysis of the dried biomass revealed that yeast biomass in this study contained mainly protein (37%) followed by carbohydrate (18.7%) and lipid (5.75%). These values meet the requirements for high quality yeast biomass production. The results of this current research would be fundamental for the future research in cultivation of local yeast strains of Laos by using glycerol waste comes from biodiesel plant for high quality biomass production.